Transformasi Sosial Melalui Pendidikan Islami: Pengabdian Masyarakat di SMP Sahabat Alam - Refi komariah; Zaitun Qamariah (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
The 65-day Merdeka Belajar Kampus Merdeka (MBKM) activity at SMP Sahabat Alam aims to support the development of students' character and skills through an Islamic education approach. The main activities include *Qur'an Time*, congregational dhuha prayer with students as the person in charge, class rule discussions, phonics journals, and learning assessments. The author also contributed to special activities such as being a camping committee, Qur'an Night, parenting, and Liqo. Through this approach, the MBKM program has succeeded in creating a conducive and inspiring educational environment, supporting students in developing their academic, social, and spiritual potential. This program also shows the importance of integrating character education into the school curriculum to form a generation that is independent, disciplined, and has an Islamic character.